2012
DOI: 10.1002/cphc.201101053
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Response of Surface‐Functionalized Metal Oxides with Well‐Matched Energy Levels: From Nothing to Something

Abstract: In recent years, an enormous amount of research has been devoted to the study of photosensitive materials from both fundamental and practical viewpoints, due to their wide applications in photocatalytic and optoelectronic devices, ultraviolet (UV) photodetectors, photoswitch microdevices, light-emitting diodes, photovoltaic devices, and photoelectrochemical cells. Metal oxides, such as ZnO, TiO(2), SnO(2), and NiO have been the most investigated photosensitive materials. To enhance and take full advantage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…1 Nevertheless, it still remains a challenge to maintain good connection between the two different constituents in the junction, which is helpful for enhancing the optoelectronic properties and charge carrier mobility. 16 Following our extensive explorations of the synthesis of the optoelectronic materials and the construction of p-n junction nanodevices, [17][18][19][20][21] here we expect to choose proper p-and n-type semiconductors to fabricate 1D core-shell heterostructures. This kind of fiber-type heterojunction is beneficial to the integration of high-quality nanodevices, due to the expanded junction area and short collection lengths of the excited carriers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Nevertheless, it still remains a challenge to maintain good connection between the two different constituents in the junction, which is helpful for enhancing the optoelectronic properties and charge carrier mobility. 16 Following our extensive explorations of the synthesis of the optoelectronic materials and the construction of p-n junction nanodevices, [17][18][19][20][21] here we expect to choose proper p-and n-type semiconductors to fabricate 1D core-shell heterostructures. This kind of fiber-type heterojunction is beneficial to the integration of high-quality nanodevices, due to the expanded junction area and short collection lengths of the excited carriers.…”
mentioning
confidence: 99%
“…24 In this communication, we have fabricated TiO 2 -PANI core-shell nanofibers via an easy method. According to our design, upon using different mechanisms of well-matched energy levels 17,18,25 and the increased thickness of the depletion region of the p-n heterojunction 21 between the TiO 2 core and the PANI shell, respectively, an increase and a decrease in photoconduction were observed in a non-oxygen and an O 2 environment, respectively.…”
mentioning
confidence: 99%
“…In recent years, an enormous amount of research has been devoted to the study of photosensitive materials, from both fundamental and practical viewpoints, due to their wide applications in photocatalytic and photoelectronic devices, ultraviolet (UV) detectors, photoswitch microdevices, light-emitting diodes, photovoltaic devices, and photoelectrochemical cells. [1][2][3][4][5][6][7] Metal oxides such as ZnO, TiO 2 and SnO 2 have been the most investigated photosensitive materials. [8][9][10] To enhance and take full advantage of the photosensitivity of metal oxides, a lot of strategies have been proposed to increase the photoresponses especially in the visible-light range, such as surface polymerization, light-element doping, or surface plasmon enhancement.…”
mentioning
confidence: 99%
“…There are some reports of photoresponse property of the PANI hybrids and also in their gel/xerogel states. In 2012, Yang et al have synthesized Bi 2 O 3 –PANI and V 2 O 5 –PANI nanocomposites showing photocurrent enhancement of 10 –2 and 10 –4 mA under UV light irradiation at 1 V, respectively . Recently, from our laboratory, Bairi et al have reported 5,5′-(1,3,5,7-tetraoxopyrrolo­[3,4- f ]­isoindole-2,6-diyl)­diisophthalic acid (PMDIG)–PANI hydrogel, which has exhibited photocurrent rectification property under white-light illumination .…”
Section: Resultsmentioning
confidence: 99%